1991
DOI: 10.1111/j.1365-2249.1991.tb02951.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of skin-infiltrating lymphocytes in atopic dermatitis

Abstract: SUMMARYSkin-infiltralitig lymphocytes (SIL) were isolated from skin biopsies of patients with hyperimmunoglobulin E (IgE) atopic dermatitis (AD) and expanded in vitro in the presence of IL-2 in combination with IL-4. Phenotypic analysis of skin-derived cells revealed the predominance of CD4+ T helper/inducer phenotype in SIL populations. In ^H-thymidine incorporation assays, SIL showed proliferation in response to lL-2, IL-3, IL-4, ionomycin (Io)+ll-o-tetradecanoyl-phorbol-Hacetate (TPA) and OKT3 -\-TPA. OKT4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 22 publications
3
36
0
Order By: Relevance
“…The mechanism and significance of local imbalance in leukocyte subsets in diseases are not well understood. It is generally accepted that autoimmune reactions were associated with the accumulation of CD4+ T cells as it has been demonstrated in rheumatoid arthritis [14,15], primary biliary cirrhosis [16], and in atopic dermatitis [17].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism and significance of local imbalance in leukocyte subsets in diseases are not well understood. It is generally accepted that autoimmune reactions were associated with the accumulation of CD4+ T cells as it has been demonstrated in rheumatoid arthritis [14,15], primary biliary cirrhosis [16], and in atopic dermatitis [17].…”
Section: Discussionmentioning
confidence: 99%
“…On serial sections, the expression of CD30 antigen was predominantly detected on CD4+ T cells. In vitro cloning studies have found that most CD4+ T cells in the lesional skin of patients with AD express a Th2-like phenotype [5, 6, 7]. CD30 expression in skin-infiltrating T cell clones of AD patients has been found to be strongly correlated with the production of IL-4 and IL-5, but to be inversely related to IFN-γ [18].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that cytokines derived from Th2 cells, such as interleukin-4 (IL-4), IL-10 and IL-13, are involved in IgE production and in the development of immediate hypersensitivity reactions [4]. In AD, a large proportion of skin-infiltrating Th cells express a Th2-like phenotype [5, 6, 7]. The production of Th2-type cytokines is associated with membrane expression of the glycoprotein CD30 in both CD4+ and CD8+ cell clones [8], and CD30 expression is regulated by IL-4 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cloning studies have provided valuable information about the functional nature of skin-infiltrating CD4+ T cells in patients with AD, as the majority of these cells express a Th2-like phenotype and some of them are specific for common environmental allergens [6, 7]. Moreover, spontaneous release of Th2-type cytokines has been demonstrated in supernatants of both peripheral blood lymphocytes and skin biopsies of AD patients [8]even if other reports suggest a potential role for IFN-γ in AD, as IFN-γ mRNA expression and not IL-4 is increased in chronic AD lesional skin [9, 10].…”
Section: Introductionmentioning
confidence: 99%